Solar-powered bidirectional charging of electric vehicle - Karthik, Nachagari; Kallakunta, Ravi Kumar; Cheerla, Sreevardhan; Mohan, Kaja Krishna; Inthiyaz, Syed; Prakash, Nelaturi Nanda; Rajanna, Bodapati Venkata; Ahammad, Sk. Hasane (International Journal of Applied Power Engineering (IJAPE), 2025)
Solar-powered bidirectional charging of an electric vehicle has three different modes of operation. The first mode of operation is “solar-powered electric vehicle charging” in which the vehicle is charged with solar energy. The second mode of operation is “grid-powered electric vehicle charging” which charges the vehicle in the absence of solar energy. The third mode of operation is “vehicle supplying to the grid” and in this mode, the vehicle energy is transferred back to the grid when there is demand to charge the other electric vehicles connected to the same grid. The system uses maximum power point tracking (MPPT) to improve power extraction from solar panels under standard test cell conditions, allowing for effective charging of electric cars. It also uses a proportional-integral (PI) controller to continually monitor the battery's state of charge (SOC). This controller modulates the duty cycle of pulse width modulation (PWM), which regulates the charging current. The charging system includes a buck-boost converter, which functions as a buck converter while supplying grid voltage to the vehicle, and a boost converter in supplying excess voltage of the vehicle to the grid. For three different modes of operation, the battery parameters such as voltage, current, and charging state are presented. The grid voltage and current are observed for the last two modes of operation.